Electro-optical modeling of InP nanowire solar cells: Core-shell vs. axial structure - Yu, Shuqing; Kupec, Jan; Witzigmann, Bernd (10th International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD 2010, 2010)
We present an investigation of the photovoltaic effect in InP nanowire arrays for both axial and core-shell structures. A microscopic electro-optical model is used to analyze the currentvoltage relationships and cell efficiencies. It is found that coreshell structures provide a larger photocurrent and efficiency yet lower open circuit voltage than an axial structure. The analysis of the p-n junction operation explains this difference and gives design guidelines for nano-photovoltaic devices. ©2010 IEEE.
CRIS-Team Scopus Importer:2021-06-11